Metamaterials: A New Ba0.6Sr0.4TiO3–Silicon Hybrid Metamaterial Device in Terahertz Regime (Small 19/2016). Issue 19 (11th May 2016) - Wu, Liang; Du, Ting; Xu, Ningning; Ding, Chunfeng; Li, Hui; Sheng, Quan; Liu, Ming; Yao, Jianquan; Wang, Zhiyong; Lou, Xiaojie; Zhang, Weili
Abstract : A giant terahertz modulation based on a Ba0.6 Sr0.4 TiO3 –silicon hybrid metamaterial is reported by L. Wu, W. Zhang, and co‐workers on page 2610. The proposed nanoscale Ba0.6 Sr0.4 TiO3 (BST) hybrid metamaterial, delivering a transmission contrast of up to ≈79% due to electrically enabled carrier transport between the ferroelectric thin film and silicon substrate, is promising in developing high‐performance real world photonic devices for terahertz technology.